Acute Ischemia Induced by High-Density Culture Increases Cytokine Expression and Diminishes the Function and Viability of Highly Purified Human Islets of Langerhans. Issue 11 (November 2017) - Smith, Kate E.; Kelly, Amy C.; Min, Catherine G.; Weber, Craig S.; McCarthy, Fiona M.; Steyn, Leah V.; Badarinarayana, Vasudeo; Stanton, J. Brett; Kitzmann, Jennifer P.; Strop, Peter; Gruessner, Angelika C.; Lynch, Ronald M.; et al.
Abstract : Background: Encapsulation devices have the potential to enable cell-based insulin replacement therapies (such as human islet or stem cell–derived β cell transplantation) without immunosuppression. However, reasonably sized encapsulation devices promote ischemia due to high β cell densities creating prohibitively large diffusional distances for nutrients. It is hypothesized that even acute ischemic exposure will compromise the therapeutic potential of cell-based insulin replacement. In this study, the acute effects of high-density ischemia were investigated in human islets to develop a detailed profile of early ischemia induced changes and targets for intervention. Methods: Human islets were exposed in a pairwise model simulating high-density encapsulation to normoxic or ischemic culture for 12 hours, after which viability and function were measured. RNA sequencing was conducted to assess transcriptome-wide changes in gene expression. Results: Islet viability after acute ischemic exposure was reduced compared to normoxic culture conditions ( P < 0.01). Insulin secretion was also diminished, with ischemic β cells losing their insulin secretory response to stimulatory glucose levels ( P < 0.01). RNA sequencing revealed 657 differentially expressed genes following ischemia, with many that are associated with increased inflammatory and hypoxia-response signaling and decreased nutrient transport and metabolism. Conclusions: In order for cell-based insulin replacement to be applied as a treatment for type 1 diabetes, oxygen and nutrient delivery to β cells will need to be maintained. We demonstrate that even brief ischemic exposure such as would be experienced in encapsulation devices damages islet viability and β cell function and leads to increased inflammatory signaling. Abstract : Human pancreatic islets under high density and hypoxic conditions similar to the ones in encapsulation devices show lower viability and insulin secretion. RNAseq analysis shows increase expression of for genes related to inflammation and hypoxia and decrease in expression of genes associated to nutrient transport and metabolism.